Depictions of escapism and gender discrimination in comic book industry - Kabir, Zarifa Tabassum (Brac University, 2021)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2021.